Pengaruh Model Discovery Learning Terhadap Keterampilan Berbicara Siswa Kelas IV Sekolah Dasar - Julia, Ike; Muhammadi, Muhammadi (Universitas Negeri Padang, 2024)
This research is motivated by the fact that there are still many students who are not able to speak in front of the class to convey their opinions. The aim of this research is to determine the effect of the Discovery Learning model on speaking skills in class IV Elementary School Region II Pauh District, Padang City. This research is quantitative, using a pretest-posttest control group design. The sampling technique is a random sampling technique. Two sample classes were selected, each of which will be used as an experimental class and a control class. The learning being compared is learning using the Discovery Learning model with learning using a conventional approach. The data collection technique uses performance test instruments. The test is assessed with the help of a speaking skills assessment rubric. Data were analyzed using the t-test. The results obtained are tcount = 2.753 and ttable = 2.006 so that tcount > ttable, namely 2.753 > 2.006, so Ho is rejected and Ha is accepted. It can be concluded that there is a influence in the speaking skills of students who are taught using the Discovery Learning model and the speaking skills of students who are taught using conventional learning in class IV Elementary School Region II Pauh District, Padang City.